Unemployment Benefits as Redistribution Scheme of Trade Gains - a Positive Analysis - Marco de Pinto (FIW - Research Centre International Economics, 2012)
Trade liberalization is no Pareto-improvement - there are winners (high-skilled) and losers (low-skilled). To compensate the losers the government is assumed to introduce unemployment benefits (UB). These benefits are financed by either a wage tax, a payroll tax, or a profit tax. Using a Melitz-type model of international trade with unionized labor markets and heterogeneous workers we show that: (i) there is a threshold level of UB where all trade gains are destroyed, (ii) this threshold differs between different kind of taxes, (iii) there is a clearcut ranking in terms of welfare for the chosen funding of the UB: 1. wage tax, 2. profit tax, 3. Payroll tax.
Keywords: F1; F16; H2; 330; trade liberalization; heterogeneous firms; trade unions; skillspecific unemployment; unemployment benefits; taxes